Development and comparison of loop-mediated isothermal amplification with quantitative PCR for the specific detection of Saprolegnia spp. - Satyaki Ghosh; David L Straus; Christopher Good; Vipaporn Phuntumart (PLoS ONE)
Saprolegniasis is an important disease in freshwater aquaculture, and is associated with oomycete pathogens in the genus Saprolegnia. Early detection of significant levels of Saprolegnia spp. pathogens would allow informed decisions for treatment which could significantly reduce losses. This study is the first to report the development of loop-mediated isothermal amplification (LAMP) for the detection of Saprolegnia spp. and compares it with quantitative PCR (qPCR). The developed protocols targeted the internal transcribed spacer (ITS) region of ribosomal DNA and the cytochrome C oxidase subunit 1 (CoxI) gene and was shown to be specific only to Saprolegnia genus. This LAMP method can detect as low as 10 fg of S. salmonis DNA while the qPCR method has a detection limit of 2 pg of S. salmonis DNA, indicating the superior sensitivity of LAMP compared to qPCR. When applied to detect the pathogen in water samples, both methods could detect the pathogen when only one zoospore of Saprolegnia was present. We propose LAMP as a quick (about 20-60 minutes) and sensitive molecular diagnostic tool for the detection of Saprolegnia spp. suitable for on-site applications.